1995
DOI: 10.1139/f95-071
|View full text |Cite
|
Sign up to set email alerts
|

Field transplantation of a freshwater bivalve, Pyganodon grandis, across a metal contamination gradient. II. Metallothionein response to Cd and Zn exposure, evidence for cytotoxicity, and links to effects at higher levels of biological organization

Abstract: To examine links between the metallothionein (MT) status of an organism and its general health, we transplanted adult specimens of the freshwater bivalve Pyganodon grandis (formerly Anodonta grandis) from a less to a more contaminated lake in the mining area of Rouyn-Noranda, in northwestern Québec. The transplanted bivalves were maintained in open enclosures placed in the bottom sediments of the contaminated lake; in addition, indigenous specimens were maintained in control enclosures in their lake of origin.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0
2

Year Published

1997
1997
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(27 citation statements)
references
References 23 publications
3
22
0
2
Order By: Relevance
“…Once bound to these carrier molecules, the metals would follow pathways that eventually lead to the observed metal distribution which includes binding to MTLP a.nd other cellular compounds. These observations have been also reported by Evtushenko et al (1986) for the scallop Mizuhopecten yessoensis, by Couillard et al (1995) for a freshwater bivalve Pyganodon grandis, and by Mouneyrac et al (1995) for C. gigas.…”
Section: Discussionsupporting
confidence: 79%
“…Once bound to these carrier molecules, the metals would follow pathways that eventually lead to the observed metal distribution which includes binding to MTLP a.nd other cellular compounds. These observations have been also reported by Evtushenko et al (1986) for the scallop Mizuhopecten yessoensis, by Couillard et al (1995) for a freshwater bivalve Pyganodon grandis, and by Mouneyrac et al (1995) for C. gigas.…”
Section: Discussionsupporting
confidence: 79%
“…Oysters exposed to Cd and Cu for 4 weeks had a MT‐like protein molar Cd/Cu ratio below 1.00, and after 2 weeks of exposure, the oyster MT‐II had a higher Cd/Cu molar ratio than the MT‐I, not unlike the results for the ZM‐MLP presented in this article [22]. Larvae from the freshwater mussel P. grandis in a contaminated lake in Québec also show very high Cu concentrations in relation to Cd amounts [23]. It is possible that the elevated Cu concentrations in the ZM‐MLP isolated here are characteristic of MT from this mussel species, although further characterization experiments are required to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 90%
“…For Cd in Littorina littorea (Langston and Zhou, 1986) a higher proportion of the metals was present in detoxified form in indigenous than in laboratoryexposed organisms. Couillard et al (1995) found clear differences in internal distribution of Cd in P. grandis, transplanted from a reference lake to a contaminated lake for 400 days compared to the indigenous mussels. In the indigenous mussels much more Cd was present in the MT fraction.…”
Section: Regression Summarymentioning
confidence: 84%